EdTech for Contexts of Forced Displacement: A Rapid Evidence Review - Barnes, Katrina; Katrin, L (EdTech Hub, 2025)
This Rapid Evidence Review provides a synthesis of recent evidence relating to the implementation of EdTech programmes, platforms, and devices for learners in contexts of forced displacement. The main aim of the review is to provide education decision-makers, funders, and implementers (among others), with a clear picture of which interventions may be the most effective in these contexts and, crucially, which implementation decisions facilitate or hinder this effectiveness. We reviewed evidence generated between 2019 and 2024 on EdTech implementations in different contexts of forced displacement. We focused on implementations aimed at primary- and secondary-age learners, as well as their teachers and caregivers. Keywords: forced displacement, refugee education, education in emergencies An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 14622107 ZenodoArchiveConcept: 14622106 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1085 2405685:KIEIX7NP
Keywords: _r:AddedByMyEducationEvidence

EdTech for Education in Emergencies: A Rapid Evidence Review - Barnes, Katrina; Ramesh Vasudevan, Sharanya; Flam, Rebekka (EdTech Hub, 2025)
This Rapid Evidence Review (RER) provides a synthesis of recent evidence relating to the implementation of EdTech programmes, platforms, and devices in emergency contexts. The main aim of the review is to provide education decision-makers, funders, and implementers (among others) with a clear picture of ‘what works’ regarding EdTech in emergencies. Crucially, it also aims to create an understanding of the conditions necessary to ensure the effectiveness of these interventions. Accordingly, the results of the review are grouped under three key themes: types of EdTech that are most effective in emergencies; barriers and challenges that limit EdTech effectiveness in emergencies; and conditions for effective implementation of EdTech in emergencies. Keywords: Education in Emergencies; EdTech; crisis contexts; remote learning An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 14617103 ZenodoArchiveConcept: 14617102 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1084 2339240:C2Z83FSW 2405685:ALBBNZDZ 2405685:BIUPGP3C
Keywords: _r:AddedByMyEducationEvidence

EdTech for Learners With Hearing and Visual Impairments: A Rapid Evidence Review for the Southeast Asian Region - Zhao, Annette; Hinks, Jessica; Thang, Sarah; Mitchell, Joel; Rabi, Asma; Ullah, Noor; Zazai, Rozina; Emerusenge, Aime Parfait; Barnes, Katrina; D'Rozario, Jonny (EdTech Hub, 2024)
This publication is one part of a series of Rapid Evidence Reviews (RERs) that has been produced by EdTech Hub as part of the ASEAN-UK Supporting the Advancement of Girls’ Education (SAGE) Programme. The programme aims to enhance foundational learning opportunities for all by breaking down barriers that hinder the educational achievements of girls and marginalised learners. The purpose of the RERs is to provide education decision-makers with accessible, evidence-based summaries of good practice in specific areas of EdTech in the Southeast Asian region. They are focused on topics which are particularly relevant to marginalised learners, and how to improve their access to education with technology. All the RERs are available at https://edtechhub.org/. This Rapid Evidence Review (RER) provides an overview of existing literature on the use of educational technology (EdTech) for the education of learners with special educational needs and disabilities (SEND) in the Southeast Asian region, specifically those with hearing and visual impairments. It summarises how EdTech is currently being used with these learners, explores how effective these implementations are, and highlights the benefits and challenges of EdTech in this context. The following countries are included in the review’s scope: Brunei, Cambodia, Indonesia, Laos, Malaysia, Myanmar, the Philippines, Singapore, Thailand, Timor-Leste, and Vietnam. The RER aims neither to advocate nor discourage the use of technology to support education forlearners with hearing and visual impairments, but rather to provide an accessible summary of existing evidence on the topic so that educators, policymakers and donors might make informed decisions about the potential role of technology in delivering education for learners with SEND. Keywords: SEND; RER; visual impairments; hearing impairments; EdTech; Southeast Asia An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 11197419 ZenodoArchiveConcept: 11197418 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1027 10.53832/edtechhub.1028 2405685:DQ9GNC3J 2405685:M6A4ZHJ3
Keywords: _r:AddedByMyEducationEvidence

Learning Continuity in Response to Climate Emergencies: Pakistan's 2022 floods - Mazari, Haani; Baloch, Imdad; Thinley, Sangay; Radford, Kate; Kaye, Tom; Perry, Freya (EdTech Hub, 2023)
Building on EdTech Hub's preliminary insights, this extended resource explores Learning continuity in response to climate emergencies following the 2022 Pakistan floods. The intention is to support stakeholders in identifying scalable and feasible ways of using EdTech in response to Pakistan’s 2022 floods and improving learning responses in future climate emergencies. We identified these approaches by interviewing flood-affected parents and teachers, government education officers, development partners, local NGOs, and international experts in education in emergencies. We find that during the different phases of response to the emergency, communities’ needs and infrastructural realities keep changing. However, existing responses to support learning have not been able to address these needs at scale. An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7334016 ZenodoArchiveConcept: 7334015 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7334016 10.5281/zenodo.7716210 10.53832/edtechhub.0135 2339240:JDMXQUFN 2405685:42XI4RCK 2405685:EQ454TF3 2405685:QEMBQCJ6 2405685:ZXRRJ5S6
Keywords: _r:AddedByZotZen; ⛔ No INSPIRE recid found

Rapid Evidence Review on Remote Teaching and Learning - Pacitto, Julia; Hayat, Amal; Hinks, Jessica; Emerusenge, Aime Parfait; Ullah, Noor; Rabi, Asma (EdTech Hub, 2025)
This Rapid Evidence Review (RER) provides a synthesis of recent evidence relating to teaching practices and pedagogies for emergency remote learning. The main aim of this review is to provide education decision-makers, funders, and implementers (among others) with a clear understanding of the available global evidence on effective practices in teaching when students are educated remotely during emergencies, and to assess the relevance of this evidence for low- and middle-income contexts. The findings of the RER are organised by the following five themes: (i) instructional design for remote learning in emergency contexts; (ii) student engagement and interactivity in emergency remote teaching; (iii) assessment, feedback, and pedagogical adaptation in remote teaching during emergencies; (iv) well-being, ‘Maslow before Bloom’, and pedagogies of care in emergency remote teaching; (v) teacher training and support in remote teaching during crises. It also identifies critical gaps in the literature on emergency remote teaching and learning, and suggest avenues for future productive research to address these gaps. Keywords: Education in Emergencies, remote learning, pedagogy, teaching methods, EdTech, emergency remote teaching An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 14967648 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1098 ZenodoArchiveConcept: 14967647
Keywords: _comingsoon; _r:AddedByMyEducationEvidence

EdTech for Education in Emergencies: A review of existing guidance and minimum standards - Barnes, Katrina; Ramesh Vasudevan, Sharanya; Hayat, Amal; Emerusenge, Aime Parfait; Zazai, Rozina (EdTech Hub, 2024)
EdTech Hub is seeking to work with the education in emergencies (EiE) sector to develop quality standards and guidance relating to the effective implementation of educational technology (EdTech) in crisis contexts. To ensure that this work is genuinely meaningful and helpful, it is important to understand what guidance is already available in this space, and what effective guidance could look like. To do this, we reviewed existing guidance documents relating to the design and implementation of EdTech in emergency contexts, along with materials from adjacent disciplines such as humanitarian work and technology design and development. By identifying key commonalities and persistent gaps across these documents, we were able to suggest what future guidance relating to EdTech in emergencies should include, and how this guidance should be developed. Keywords: EdTech; education in emergencies; guidance; minimum standards An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 14051241 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1068 ZenodoArchiveConcept: 14051240
Keywords: _r:AddedByMyEducationEvidence

Using EdTech in Settings of Fragility, Conflict and Violence: A Curated Resource List - Koomar, Saalim; Moss Coflan, Caitlin; Kaye, Tom (EdTech Hub, 2020)
This curated list of resources collates interventions that effectively deploy education technology in settings of fragility, conflict and violence (FCV). This list explores effective uses of EdTech in FCV settings, emphasising interventions and evidence relevant to the Yemeni context and distance learning during the Covid-19 crisis.
previousshortDOI: 10/ghgng4 previousDOI: 10.5281/zenodo.3885806 EdTechHub.Source: 2405685:CMS6HPI8 EdTechHub.Source: <this> shortDOI: 10/ghgng4 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3875138 10.5281/zenodo.3885806 10.53832/edtechhub.0042 10/ghgng4 2129771:FCNVWJUI 2129771:VJXKA7AN 2339240:FEGWVFS3 2339240:FJ5LQ7QK 2405685:79LULMUU 2405685:BTWBKYN7 2405685:CMS6HPI8 2405685:HLCYI98H 2405685:RV5RNCII
Keywords: C:Yemen; F: Helpdesk response; LP: English; W:Fragile and conflict affected contexts; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v1; _zenodoETH; dode_eth-src-eth; dode_eth-trf2-dode

EdTech in Liberia: A Rapid Scan - Upadhyay, Arjun; Taddese, Abeba (EdTech Hub, 2020)
EdTech Hub country scans explore factors that enable and hinder the use of technology in education. These factors include the policy or vision for EdTech, institutional capacity, private sector partnerships, and digital infrastructure. The scans are intended to be comprehensive but are by no means exhaustive. The aim is to provide a useful starting point for more in-depth discussions about opportunities and barriers in EdTech in specific countries and, in this case, Liberia. This report is based primarily on desk research, with quality assurance provided by a country expert.
ZenodoArchiveID: 5652130 previousZenodoArchiveID: 3830953 previousshortDOI: 10/ghgk68 previousDOI: 10.5281/zenodo.3830953 shortDOI: 10/ghgk68 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3830953 10.53832/edtechhub.0033 10/ghgk68 2339240:XCBTX2XL 2405685:2HM2SBVM 2405685:FU7Z8QM7
Keywords: C:Liberia; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v1; _zenodo:submitted; _zenodoETH

Refugee Education: A Rapid Evidence Review - Ashlee, Amy; Clericetti, Giulia; Mitchell, Joel (EdTech Hub, 2020)
This Rapid Evidence Review (RER) provides an overview of existing literature on the use of educational technology (EdTech) for education of refugees in low- and middle-income countries (LMICs). The RER has been produced in response to the widespread global shutdown of schools resulting from the outbreak of Covid-19. It therefore has an emphasis on transferable insights that may be applicable to educational responses resulting from the limitations caused by Covid-19. In the current global context, lessons learnt from the use of EdTech in refugee contexts — in which education is often significantly disrupted and education systems and responses are required to rapidly adapt — are salient.
ZenodoArchiveID: 4557019 PreviousDOI: 10.5281/zenodo.4477154 PreviousShortDOI: 10/ghgnf2 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3901521 10.5281/zenodo.4557019 10/ghgnf2 2339240:3KCTC7UA 2339240:5B7T9LEG 2339240:K45TP2GI 2339240:NNZ9DD54 2339240:SIV6ZELZ 2339240:W3ALIEA9 2405685:397HVPFN 2405685:4M9GTG8I 2405685:5AWZGNCG 2405685:6EUNRYPS 2405685:E56IKGK2 2405685:E6DMTNLL 2405685:TXGBLY4U 2405685:UUNEJ7FS 2405685:W9JLL7JV
Keywords: L:Refugees and migrants; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _P:Evidence review VCMFM9ZD; _cover:v3; _zenodo:submitted; _zenodoETH

Minoritised Languages, Education, and Technology: Current practices and future directions in low- and middle-income countries - Zhao, Annette; Mitchell, Joel; Gasanabandi, Gentille; Ullah, Noor; Barnes, Katrina; Koomar, Saalim (EdTech Hub, 2024)
This article explores the current status and future directions of mother-tongue-based multilingual education (MTB MLE) and the use of technology in low- and middle-income countries (LMICs), focusing on the use of minoritised mother tongues. An initial literature review of available academic sources in multiple languages reveals a lack of evidence on the use of technology in MTB MLE across different countries, especially multilingual contexts with greater linguistic diversity. To understand the issue in greater detail and to offer recommendations informed by current practice, interviews and a collaborative workshop with four organisations with relevant educational technology (EdTech) initiatives were conducted. The analysis covers facilitating and limiting factors these organisations have encountered, and the potential positive impact on learners and society generally. We conclude by identifying practical, policy, and research priorities for multilingual education and educational technology in general.
ZenodoArchiveID: 7267302 ZenodoArchiveConcept: 7267301 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7267302 10.53832/edtechhub.0127 2339240:V7ARHU93 2405685:GBBGHCBH 2405685:QADQUWU3 2405685:UTTZNZ24
Keywords: _r:AddedByZotZen

Education in Emergencies: A Rapid Evidence Review - Mitchell, Joel; Ashlee, Amy; Clericetti, Giulia; Gladwell, Jessica; Torrance, Rebecca (EdTech Hub)
PreviousDOI: 10.5281/zenodo.4476897 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4476897 10.5281/zenodo.4556940 2339240:GU8FEH69 2339240:W9GJBGT9 2405685:FEXJQ37Q 2405685:ZPTMAP5C
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _zenodoETH

Low-Tech Devices and Connectivity for Learning in Lebanon - Chuang, Rachel; Khalayleh, Abdullah (EdTech Hub, 2021)
This document was produced in response to a request from the FCDO Lebanon team for guidance on leveraging low-tech devices and enabling connectivity to support learners in Lebanon, aligning with school reopenings. The document compiles effective initiatives across Lebanon and other countries.
ZenodoArchiveID: 4140412 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4140412 2129771:9X3BTTLU 2339240:9PYYNK6J 2405685:ISTFVCA7 2405685:NS927T5K
Keywords: F: Helpdesk response; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _zenodo:submitted; _zenodoETH; dode_eth-src-eth; dode_eth-trf2-dode